The Relationship between Age, Gender, and Physical Inactivity on the Incidence of Obesity at Puskesmas Johar Baru, Central Jakarta - Johannes Ginting; Tri Suci (Universitas Widya Gama Mahakam Samarinda, 2024)
Background: Obesity is an increasing global health challenge, including in Indonesia. Objectives: This study was intended to explore the correlation between age, gender, and physical activity level with the incidence of obesity. Research Methods: This study used secondary data from Puskesmas Johar Baru, Central Jakarta, in 2021, with a sample size of 72,680 patients; the number of patients who were obese was 22,297 people. Data processing was performed using SPSS 25 software, involving bivariate analysis using the Chi-Square test and multivariate analysis using multiple logistic regression with the enter method at a significance level 0.05. Results: The results showed that the majority of obese respondents were of productive age, as many as 17,521 people (p-value 0.000), female gender as many as 9,441 people (p-value 0.000), and stated that they lacked physical activity as many as 17,207 people (p-value 0.000). Statistically, through the Chi-Square test, it was found that there was a significant association between the incidence of obesity and the three variables, with a p-value ≤ 0.05. Multivariate analysis using logistic regression reinforced that gender emerged as the dominant factor, with females having a 12.925 times higher risk of being obese compared to males. Conclusion: These findings underscore the importance of gender variables in the context of obesity in Puskesmas Johar Baru. This study highlights the differences in obesity prevalence by age and gender. Middle-aged adults, particularly women, are more prone to obesity. Physical inactivity was also identified as a significant factor in the increased prevalence of obesity. These results have implications for developing more specific obesity prevention interventions, especially for women.